Increased circulating resistin is associated with insulin resistance, oxidative stress and platelet activation in type 2 diabetes mellitus - Santilli, Francesca; Liani, Rossella; Di Fulvio, Patrizia; Formoso, Gloria; Simeone, Paola; Tripaldi, Romina; Ueland, Thor; Aukrust, Pål; Davì, Giovanni (Thrombosis and Haemostasis, 2016)
Resistin is an adipokine that promotes inflammation and insulin resistance by targeting several cells including platelets. We hypothesised that in type 2 diabetes (T2DM), resistin may foster in vivo oxidative stress, thromboxane-dependent platelet activation and platelet-derived inflammatory proteins release, key determinants of atherothrombosis. A cross-sectional comparison of circulating resistin, sCD40L, as a marker of platelet-mediated inflammation, asymmetric dimethylarginine (ADMA), endothelial dysfunction marker, Dickkopf (DKK)-1, reflecting the inflammatory interaction between platelets and endothelial cells, and urinary 8-iso-PGF2α and 11-dehydro-TxB2, reflecting in vivo lipid peroxidation and platelet activation, respectively, was performed between 79 T2DM patients and 30 healthy subjects. Furthermore, we investigated the effects of the α-glucosidase inhibitor acarbose and the PPARγ agonist rosiglitazone, targeting hyperglycaemia or insulin resistance, versus placebo, in 28 and 18 T2DM subjects, respectively. Age- and gender-adjusted serum resistin levels were significantly higher in patients than in controls. HOMA (β=0.266, p=0.017) and 11-dehydro-TXB2 (β=0.354, p=0.002) independently predicted resistin levels. A 20-week treatment with acarbose was associated with significant reductions (p=0.001) in serum resistin, DKK-1, urinary 11-dehydro-TXB2 and 8-iso-PGF2α with direct correlations between the change in serum resistin and in other variables. A 24-week rosiglitazone treatment on top of metformin was associated with significant decreases in resistin, DKK-1, 11-dehydro-TXB2 and 8-iso-PGF2α, in parallel with HOMA decrease. In conclusion, resistin, antagonising insulin action in part through PPARγ activation, may favour insulin resistance and enhance oxidative stress, endothelial dysfunction and platelet activation. The adipokine-platelet interactions may be involved in platelet insulin resistance and their consequent pro-aggregatory phenotype in this setting.
Keywords: Diabetes mellitus; adipokine; insulin resistance; oxidative stress; platelet activation